Perbedaan Lama Pelepasan Tali Pusat Dengan Pemotongan Tali Pusat Segera Setelah Lahir Di BPM Satria Siswihipni Dan BPM Tety Septiana Jati Agung Lampung Selatan - Vida Wira Utami; Anggraini Anggraini; Ely Rachmawati (Malahayati Nursing Journal, 2021)
ABSTRACT: DIFFERENCES IN THE DELIVERY OF THE CORNER WITH THE CUTTING OF THE CORNER IMMEDIATELY AFTER BIRTH AT BPM SATRIA SISWIHIPNI AND BPM TETY SEPTIANA JATI AGUNG SOUTH LAMPUNG Intriductions: Based on the 2019 South Lampung Health Office Profile, there were 23 cases of neonatal death, 1 case of infant death, and no under-five mortality.  The highest causes of death are asphyxia, low birth weight, and infection.  The Jati Agung area is one of the contributors to the morbidity of umbilical cord infection in neonates.  The importance of a unified approach to maternal and infant care, and clearly stated.  With the delay in clamping, the baby will get an additional 50-100 ml of blood, known as a placental transfusion (Aprilia, 2011). Purpose: The purpose of the study was to find out the difference in the length of umbilical cord detachment with cutting the umbilical cord immediately after birth at BPM Satria Siswihipni and BPM Tety Septiana Jati Agung, South Lampung in 2021.Methode: This type of research uses quantitative approach to control time series design.  The population in this study were all mothers giving birth at BPM Satria Siswihpni and BPM Tety Septiana Jati Agung, South Lampung with an average of 45 deliveries and 48 deliveries.  The sample in this study were 30 respondents, 15 control groups, 15 intervention groups. The sampling technique used Accidental Sampling.  Data analysis techniques are Univariate Analysis and Bivariate Analysis with independent t-testResult: Univariate analysis results showed that the average value of umbilical cord detachment with delay was 3.93, standard deviation 1.033.  The mean value of immediate cut release was 5.93, standard deviation 1.580.  The results of the bivariate t test obtained a value of (p = 0.000).Conclusion: there were difference in the length of the release of the umbilical cord with cutting the umbilical cord immediately after birth with a delay in cutting the umbilical cord at BPM Satria and BPM Tety, South Lampung in 2021. It is expected that health workers will postpone cutting  umbilical cord in BBL. Keywords: umbilical cord detachment, immediate cutting, delaying umbilical cord cuttingINTISARI:PERBEDAAN LAMA PELEPASAN TALI PUSAT DENGAN PEMOTONGAN TALI PUSAT SEGERA SETELAH LAHIR DI BPM SATRIA SISWIHIPNI  DAN BPM TETY SEPTIANA  JATI AGUNG LAMPUNG SELATAN.  Latar Belakang: Berdasarkan Profil Dinas Kesehatan Lampung Selatan Tahun 2019, terdapat 23 kasus kematian neonatal, 1 kasus kematian bayi, dan tidak ada kematian balita. Penyebab kematian tertinggi yaitu asfiksia, BBLR, dan infeksi. Wilayah Jati Agung salah satu penyumbang angka kesakitan infeksi tali pusat pada neonatal. Pentingnya penyatuan pendekatan asuhan ibu dan bayi, dan menyatakan dengan jelas. Dengan ada nya penundaan pengkleman bayi akan mendapatkan tambahan 50-100 ml darah yang dikenal dengan transfuse plasenta (Aprilia, 2011). Tujuan penelitian diketahui Perbedaan Lama Pelepasan Tali Pusat Dengan Pemotongan Tali Pusat Segera Setelah Lahir Di BPM Satria Siswihipni  dan BPM Tety Septiana  Jati Agung Lampung Selatan Tahun 2021.Metode Penelitian: jenis penelitian menggunakan kuantitatif dengan pendekatan control time series design. Populasi dalam penelitian ini adalah semua ibu bersalin di BPM Satria Siswihpni dan BPM Tety Septiana Jati Agung Lampung Selatan dengan rata-rata 45 persalinan dan 48 persalinan. Sampel dalam penelitian ini sebanyak 30 responden, 15 kelompok control, 15 kelompok intervensi.Teknik sampling menggunakan Accidental Sampling. Teknik analisa data yaitu Analisa Univariat dan Analisa Bivariat dengan Uji t independentHasil :Hasil Analisis Univariat menunjukkan nilai rata-rata pelepasan tali pusat dengan penundaan adalah 3,93, standar deviasi 1,033. Nilai rata-rata pelepasan pemotongan segera adalah 5,93, standar deviasi 1,580. Hasil bivariat dengan uji t didapatkan nilai (p=0,000) artinya Kesimpulan: Ada perbedaan lama pelepasan tali pusat dengan pemotongan tali pusat segera setelah lahir dengan penundaan pemotongan tali pusat di BPM Satria dan BPM Tety Lampung Selatan Tahun 2021. Diharapkan bagi tenaga kesehatan untuk melakukan penundaan pemotongan tali pusat pada BBL Kata Kunci     : Pelepasan Tali Pusat, Pemotongan segera, tunda pemotongan tali pusat